PENGARUH TERAPI MUSIK TERHADAP PERUBAHAN TINGKAT DEPRESI PADA LANSIA DI PSTW (PANTI SOSIAL TRESNA WREDHA) UNIT BUDI LUHUR, KASONGAN, BANTUL YOGYAKARTA - Sri Eko Purbowinoto; Kartinah Kartinah (Jurnal Berita Ilmu Keperawatan, 2011)
The increasing of a person's age will be accompanied by a variety of physical, psychological and social setbacks. Psychological deterioration is often encountered in the elderly such as feeling useless, easily upset, insomnia, stress, and depression. One way of therapy used for the elderly to reduce the level of depression is the use of keroncong music therapy. The results of preliminary studies of the interviews showed three people claim to have difficulties sleeping at night, and sometimes feel afraid when there is an earthquake. Two elderly people that would rather be alone than to gather with other seniors, and 1 elderly claimed almost every day has no appetite. The research objective is to determine the effect of music therapy to changes in rates of depression in the elderly in PSTW (Panti Sosial Tresna Wredha) Budi Luhur’s Unit, Kasongan, Bantul, Yogyakarta. This type of research is quantitative. The design of experimental research with pre-posttest design tets. Large of sample was 52 respondents with using a sampling technique was purposive sampling. the instrument uses a questionnaire study of depression.the comparative test analysis tools using Wilcoxon Rank test. Results showed before keroncong music therapy given there are 21 people with mild depression (77.8%), moderate depression was 6 people (22 , 2%), after being given keroncong music therapy one respondent (3.7%) were depressed, 12 people (44.4%) had mild depression, 14 people (51.9%) became normal. the test results of Wilcoxon Rank test shows the value of Z = -2.412 and p = 0.016. So that concluded there is the influence of music therapy to changes the rates of depression to the elderly in PSTW (Panti Sosial Tresna Wredha) Budi Luhur’s Unit, Kasongan, Bantul, Yogyakarta.